Comparative life cycle assessment of WTaTiVCr high-entropy alloy fabricated by mechanical alloying and 3D mixing methods - Feng, Jiarui; Pagone, Emanuele; Waseem, Owais Ahmed (Springer, 2026)
WTaTiVCr High-Entropy AlloysHigh-entropy alloy (HEAs) are recognized as promising candidates for fusion plasma-facingFusion plasma-facing materials applications. However, the environmental impact of their development and fabrication methods remains insufficiently characterized. This study presents a comparative evaluation of two powder processing routes: mechanical alloying by ball milling and low-shear 3D mixing. Both fabrication methods yield single-phase, Body-Centred Cubic WTaTiVCr HEAs with comparable Vickers hardness and relative densities exceeding 98%. Applying a “cradle-to-gate” (i.e. from raw material production to arc plasma sintering) Life Cycle Assessment method, the carbonCarbon footprint of both routes is estimated to produce the divertor surface of the International Thermonuclear Experimental Reactor. The findings identify the more environmentally friendly route as well as carbonCarbon footprint “hotspots”. Results for the alloy with 30% of tungsten molar content show a carbonCarbon footprint reduction of 48.76 tCO2e, when switching from the ball milling to the 3D mixing manufacturing route. Such difference grows by a further 35% when the tungsten content increases up to 90% molar fraction.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 12 Responsible Consumption and Production; High-Entropy Alloy; Sustainability; Extraction and Processing; Fusion Plasma-Facing Materials